2016
DOI: 10.3390/su8090929
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Residential Demand Response through Dynamic Pricing Schemes: A Behavioural Review of Smart Grid Pilots in Europe

Abstract: Abstract:Many smart grid projects make use of dynamic pricing schemes aimed to motivate consumers to shift and/or decrease energy use. Based upon existing literature and analyses of current smart grid projects, this survey paper presents key lessons on how to encourage households to adjust energy end use by means of dynamic tariffs. The paper identifies four key hypotheses related to fostering demand response through dynamic tariff schemes and examines whether these hypotheses can be accepted or rejected based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 24 publications
2
48
0
Order By: Relevance
“…However, this result contrasts other findings in the literature. For example, Kessels et al [38] have found that understanding of the tariff is significant for behaviors changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this result contrasts other findings in the literature. For example, Kessels et al [38] have found that understanding of the tariff is significant for behaviors changes.…”
Section: Discussionmentioning
confidence: 99%
“…Some facts support the necessity to have these trends. Firstly, the literature reports some problems in the case of manual control of demand by customers [58]. Secondly, enabling technology improves response and flexibility [29,35].…”
Section: Linkage Between Pdr Economic Model and Pblmmentioning
confidence: 99%
“…Thirdly, ICT is becoming more and more widespread and ICT costs are also falling. In this way, flexibility should be provided by smart appliances to obtain larger and more predictable demand shifts [58,59]. This enabling technology needs some inputs from these observed trends of flexible demand.…”
Section: Linkage Between Pdr Economic Model and Pblmmentioning
confidence: 99%
“…However, decreasing peak loads and, thereby, using the grid infrastructure more efficiently depend strongly on the involvement of single grid users [44]. Dynamic electricity tariffs can facilitate consumer engagement and behaviour change in form of shifting demand [45]. Yet, in the projects that fall under the Experimentation Decree, dynamic electricity tariffs are only mentioned in three cases.…”
Section: More Efficient Use Of Grid Infrastructure and Involvement Ofmentioning
confidence: 99%